KEPUTUSAN PEMBELIAN MAHASISWA PADA PRODUK ONLINE SHOP SHOPEE DAN FAKTOR PENENTUNYA - Heru Ependi; Reza Widhar Pahlevi (Program Studi Manajemen, 2021)
Abstract The purpose of this study is to find out what factors determine online consumer purchasing decisions at Shopee and how the online consumer purchasing decisions process at Shopee. The research approach used is a qualitative descriptive approach. Research related to consumer online purchasing decision factors at Shopee, the object to be studied is consumers who use the Shopee application. In social situations or research objects, the object of this research is the students of the Faculty of Economics, Cokroaminoto University, Yogyakarta, who actively use the Shopee application as a place to shop online, and who are considered to meet or know the research criteria. Based on the results of the discussion that the promotions implemented in the Shopee e-commerce store, such as the application of discount promotions, free shipping promotions, prices, product quality and trust given by the Shopee company, affect consumers' online purchasing decisions at Shopee and then the online consumer decision process. preceded by, problem recognition, information search, evaluation of alternatives, purchase decisions, post-purchase behavior, influenced by many factors. These factors can be internal factors, namely consumer psychology, and external factors, which consist of the socio-cultural environment of the community, marketing stimuli, and vendor control systems which include time efficiency in seeking competitive prices and good quality.